PENGARUH DISIPLIN KERJA TERHADAP PRESTASI KERJA GURU SMA NEGERI 4 BANDUNG - Andini Dwi Fitriani (Jurnal Tata Kelola Pendidikan, 2021)
This research generally aims to reveal a clear picture of the effect of work discipline on teacher work performance. The research method used is a descriptive method supported by literature studies and by quantitative approaches. The population in this study was 30 respondents from teachers of SMA NEGERI 4 Bandung. Wms data processing results (Weight Means Score) that has been processed obtained the average result of variable score X of 4.27 which belongs to a very high category. As for variable Y obtained an average score of 4.04 which belongs to a very high category. Based on the results of the Normality Test, each variable is obtained that the calculated X2 value of variable X is 7,975 the value of X2 table value is 11,070, it is declared normally distributed, while variable Y value X2 calculates 5,798 the table X2 value is 12,592, it is declared normal distribution. Based on the results of the Correlation Coefficient Test obtained by the price of correlation coefficient (r) variable X to variable Y positive direction of 0.99, it can be concluded that the correlation coefficient between the two variables is at a very strong correlation coefficient level. Based on the results of the calculation of significant tests obtained the price of 1 count of 37.05 and the price of t table of 2,045, the correlation of variable X to variable Y is significant. While the coefficient of variable determination X terhdap variable Y by 98.01%. It can be concluded that the increase and decrease in teacher work performance is determined by the teacher's own work discipline of 98.01%, while the remaining 1.99% is determined by other factors. Based on the calculation result obtained price a and price b of 0.983, so the regression equation that describes the predicted score of variable direction Y based on variable X is Y = 0 + 0.983 X. The difference in the overall statistics test results can be concluded that " There is a Significant Influence between Work Discipline On The Prestassi Work of Teachers SMA NEGERI 4 Bandung ", proven to be true or acceptable.